Pentingnya Pembelajaran IPS Melibatkan Permainan Tradisional dalam Meningkatkan Karakter Perserta Didik (Studi Kasus Taman Baca Masyarakat Lingkaran Kecamatan Pantai Labu Kabupaten Deli Serdang) - Andre Agasi (Proceedings Series on Social Sciences & Humanities, 2023)
At present the existence of traditional games in the midst of people's lives is starting to disappear with the development of technology that is increasingly advanced and fast. The entry of modern culture can cause the disappearance of a culture including traditional games. This paper focuses on the importance of social studies learning involving traditional games in improving children's character. The research method used is qualitative research. The results of this study are the first, with traditional games children will always give birth to a feeling of joy. second, children's enthusiasm is always honed, Third, games using materials, Fourth, through games children begin to recognize the model of participatory education. Traditional games which are quite diverse need to be explored and developed because they contain values such as honesty, sportsmanship, tenacity and mutual cooperation.